Fatores prognósticos para o óbito neonatal em gestações com diástole zero ou reserva na dopplervelocimetria das artérias umbilicais - Martins Neto, Manoel (2009)
Objectives: evaluate the perinatal results in pregnancies with fetal brain sparing on the Doppler velocimetric study and identify the main prognostic factors associated with neonatal death. Methods: it is a transverse study from the charts of pregnant wowen with diagnosis of brain sparing, absent or reversed end-diastolic flow in the umbilical artery, followed at the Service of Maternal-Fetal Medicine of Maternidade-Escola Assis Chateaubrind – Universidade Federal do Ceará. There were analyzed 143 patients with single pregnancies, without structural or chromosomal anomalies, presenting gestacional age above 22 weeks and fetal weight equal or above 500 grams. ROC curve was constructed for gestacional age and weight at birth (independent variables) and neonatal death (dependent variable). The perinatal results were evaluated on the general population and on each group (brain sparing, absent and reversed end-diastolic flow), later compared with each other. For the statistical analisys it was utilized the tests: Shapiro-Wilk, Levene, t Studente, Mann-Whitney, ANOVA, Kruskal Wallis, Fisher. Chi-square, Logistical and Multinomial Regression. All were considered statistically significant when p < 0.05. Results: the majority of pregnante wowen (78.3%) presented some hypertensive disturb associated to the pregnancy. The pregnancy was resolved in the first 24 hours after Doppler velocimetric diagnosis on most cases (74.8%), being the abdominal acess utilized in 96.5% of the times. At the moment of delivers, the average gestational age was 33.6 weeks and the weight was 1684g. The newborns were classified as small for gestational age in 69.6% and needed ICU admission in 63% of the cases. The indexes of perinatal mortality for brain sparing, absent and reversed end-diastolic flow were respectively 11.1, 31.1 and 70.6%. The weight of the newborn (area bellow the ROC curve 0.934, p=0.000 and gestational age at birth (area 0.909, p=0.000) have shown to be good predictors of neonatal death. The cutoff point calculated for the weight was 1010g and for the gestational age as 32.5 weeks. The incidence of diminished amniotic fluid indez (AFI) in the pregnancies with lethal perinatal outcome was 41.2% and in those without lethality was 41.3%. Conclusions: fetuses with diagnosis of brain sparing, absent and reversed end-diastolic flow presented progressively worse and statistically different with each other prognosis. The gestational age and weight at birth showed excellent correlation with neonatal mortality. The AFI did not demonstrate association with lethality rate.